MANAGEMENT OF FACILITIES AND INFRASTRUCTURE IN RELIGION-BASED PRIMARY SCHOOLS IN IMPROVING THE QUALITY OF LEARNING: OPTIMIZATION AND DEVELOPMENT STRATEGIES - Nisa, Kamilatun; Bastian, Fanny Adam; Rahmi, Talitha; Sibula, Irvine; Suprianto, Matius Eko; Anse, Frederikus M. K. (Idaarah: Jurnal Manajemen Pendidikan, 2024)
In this study, it is written about changes from era to era that demand better quality education and learning quality, supported by the optimization of all educational infrastructure in an efficient and effective manner. These demands must be met by every institution in the field of education, so that every educational institution must be able to analyze and evaluate a problem in its institution through the SWOT analysis model. Furthermore, they are able to find solutions, development strategies, and ways to optimize the quality of institutional learning. The qualitative approach used in this study analyzes and understands the situation objectively through observation, interviews, and documentation studies at an Islamic elementary school. To determine the strategy, an analysis of the situation on internal and external variables in the educational environment is required. According to the study’s findings, the school already has good and adequate infrastructure and requires optimization of facility and infrastructure management in order to improve the quality of learning at SD Islam Melati Nusantara, Gresik Regency.